PENGARUH RETURN ON ASSET DAN PAJAK TERHADAP PRAKTIK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewi, Nurma Gupita; Hidayat, Riskin (JAB (Jurnal Akuntansi & Bisnis), 2018)
The aim of this study to examine the influence of return on asset and tax toward income smoothing practice among manufacture sector listed at Indonesia Stock Exchange. The population in this study are all companies listed on the Indonesia Stock Exchange during the period 2013-2015. This study uses purposive sampling and takes some criterias. The samples consists of 81 observations. The variables used in this study is return on asset and tax. The analysis technique is logistic regression analysis. The results of this study indicate that return on assets has a positive and insignificant effect on income smoothing and tax has a significant negative effect on income smoothing practices. Â Keywords: income smoothing, return on asset, tax and manufactur sector